IMPERATIVES OF NIGERIA’S FOREIGN POLICY UNDER THE LEADERSHIP OF PRESIDENT BOLA AHMED TINUBU - SAMUEL NAANSUAN DAWAM; SOLOMON JANG ARIN (International Studies Journal)
This paper explores the critical elements of Nigeria’s foreign policy under the current leadership of President Bola Ahmed Tinubu. It delves into the strategic decisions, policy changes, and diplomatic initiatives so far undertaken during the last six months of his administration. Using documentary sources, the paper further examines the impact of these policies on Nigeria’s international relations, economic growth, and regional stability. It also provides an analysis of the challenges encountered and the strategies employed to overcome them. The study concludes with an assessment of the effectiveness of President Tinubu’s foreign policy and its implications for Nigeria’s future diplomatic engagements. This paper aims to contribute to the understanding of Nigeria’s foreign policy dynamics and offer insights for policy formulation and implementation.